Hands-on Science. Advancing Science. Improving Education - Costa, Manuel F. M. (2018)
The book herein aims to contribute to the advancement of Science to the improvement of Science Education and to an effective implementation of a sound widespread scientific literacy at all levels of society. Its chapters reunite a variety of diverse and valuable works presented in this line of thought at the 15th International Conference on Hands-on Science “Advancing Science. Improving Education”